Power Inhibition of ExtractsAzolla microphyllaagainst the Growth of Pathogenic Bacteria (Vibrio alginolyticus, Escherichia coli and Aeromonas hidrophylla - Aznardi, Shodikin; Yoswaty, Dessy; Efendi, Irwan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT The research was conducted in February - April 2017 at the Laboratory of Marine Chemistry and Marine Microbiology Laboratory, Riau University and Integrated Chemical Laboratory, Muhammadiyah University of Riau. The purpose of this study was to determine the inhibitory power of Azolla microphylla extracts cultured in 5ppt saline water to the growth of pathogenic bacteria (V. alginolyticus, E. coli and A. hidrophylla). Inhibitory test using 4 concentrations used are 100%, 50%, 25% and 12.5%. The results showed that the antimicrobial content of A. microphylla extract could inhibit the growth of pathogenic bacteria (V. alginolyticus, E. coli and A. hydrophylla) with weak ability with inhibitory zone diameter between 0.15 - 2.15 mm. Keyword: ExtractA. microphylla, Power Inhibition, Pathogenic Bacteria